Penguatan Ekonomi Kreatif Berbasis Potensi Lokal di Desa Dombu, Kabupaten Sigi - Ani Susanti; Mukarramah Mukarramah; Mohamad Saleh (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The creative economy has become one of the key pillars in economic development in Indonesia, including in Dombu Village, Sigi Regency. This article aims to explore the local potential that can support the strengthening of the creative economy in the village. By analyzing various aspects, ranging from natural resources and local culture to community initiatives, this study is expected to provide a clear overview of strategies that can be implemented to maximize the potential of the creative economy. Using a qualitative approach and secondary data analysis, the findings indicate that the development of the creative economy in Dombu Village can be achieved through collaboration between the government, the community, and the private sector.